2022
DOI: 10.1093/noajnl/vdac095
|View full text |Cite
|
Sign up to set email alerts
|

Targeting protein arginine methyltransferase 5 sensitizes glioblastoma to trametinib

Abstract: Background The prognosis of glioblastoma (GBM) remains dismal because therapeutic approaches have limited effectiveness. A new targeted treatment using MEK inhibitors, including trametinib, has been proposed to improve GBM therapy. Trametinib had a promising preclinical effect against several cancers but its adaptive treatment resistance precluded its clinical translation in glioblastoma. Previously, we have demonstrated that Protein Arginine Methyltransferase 5 (PRMT5) is upregulated in GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Vinblastine shows sensitivity for both LGG and GBM [ 40 , 41 ] and it is in clinical trials for the treatment of these cancers. Other drugs such as Olaparib [ 42 ], Crizotinib [ 43 ], and Trametinib [ 44 ] have also shown encouraging results for the treatment of brain cancer. Our findings, along with those from the existing literature, suggest that the current approach may be used to aid in clinical decision-making for the treatment of gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…Vinblastine shows sensitivity for both LGG and GBM [ 40 , 41 ] and it is in clinical trials for the treatment of these cancers. Other drugs such as Olaparib [ 42 ], Crizotinib [ 43 ], and Trametinib [ 44 ] have also shown encouraging results for the treatment of brain cancer. Our findings, along with those from the existing literature, suggest that the current approach may be used to aid in clinical decision-making for the treatment of gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, in GB, MTAP is one of the most frequently deleted genes 67 —although it has been shown that the success of PRMT5 inhibition in the context of GB is also dependent on other factors 68 . Still, PRMT5 inhibitors are increasingly studied in the context of both GB cell lines and primary cells 68 , 69 , and some reports also indicate inverse correlation between the PRMT5 expression levels and survival of patients with glioma or GB diagnosis 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, for tumors with overexpressed PRMT5, PRMT5 inhibitors can be investigated in combination with common chemotherapeutic agents to overcome chemoresistance. Indeed, the combination of the PRMT5 inhibitor, JNJ-64619178, and trametinib in glioblastoma displayed an increase in the number of apoptotic cells and number of cells in G1 cell cycle arrest than either individual therapy alone [ 56 ]. Thus, health care providers should also consider assessing the expression of PMTs when determining combinational drug regimens for individual cancer patients.…”
Section: Discussionmentioning
confidence: 99%